2020
DOI: 10.1101/2020.09.30.320655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Momilactone B inhibits Arabidopsis growth and development via disruption of ABA and auxin signaling

Abstract: In competition for limited resources, many plants release allelochemicals to inhibit the growth of neighboring plants. Momilactone B (MB) is a major allelochemical produced by rice (Oryza sativa), however its mode of action is currently unknown. We used Arabidopsis (Arabidopsis thaliana) as a model system to evaluate potential mechanisms underlying the inhibitory effects of MB on seed germination, seedling establishment and root growth through the use of confocal microscopy and the examination of transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(117 reference statements)
1
3
0
Order By: Relevance
“…Coumarin strongly affected root morphology, causing a primary root reduction and increasing lateral root number and root hair length in Arabidopsis seedlings [ 27 ]. Similar results were observed with monoterpene citral [ 28 ], sesquiterpenoid nerolidol [ 20 ], alkaloid norharmane [ 25 ], and momilactone B [ 29 ]. All the authors suggested that these allelochemicals might alter the root system, affecting both the auxin signalling pathway and transport, and interfering with its spatio-temporal homeostasis.…”
Section: Introductionsupporting
confidence: 78%
“…Coumarin strongly affected root morphology, causing a primary root reduction and increasing lateral root number and root hair length in Arabidopsis seedlings [ 27 ]. Similar results were observed with monoterpene citral [ 28 ], sesquiterpenoid nerolidol [ 20 ], alkaloid norharmane [ 25 ], and momilactone B [ 29 ]. All the authors suggested that these allelochemicals might alter the root system, affecting both the auxin signalling pathway and transport, and interfering with its spatio-temporal homeostasis.…”
Section: Introductionsupporting
confidence: 78%
“…These compounds can inhibit growth by affecting cell division, nutrient uptake, photosynthesis, and hormone balance [ 88 , 89 ]. For instance, momilactones may act as auxin inhibitors, whereas polyacetylenes can inhibit mitochondrial respiration [ 90 ]. The generation of reactive oxygen species leading to oxidative damage is another potential mode of action [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coumarin compounds also could affect the growth and development of plants by regulating their endogenous hormone levels. Gibberellins (GA) and abscisic acid (ABA) are two vital hormones and play important roles in seed germination 20,21 . GA could induce amylase synthesis, promote starch metabolism and provide energy for seed germination.…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellins (GA) and abscisic acid (ABA) are two vital hormones and play important roles in seed germination. 20,21 GA could induce amylase synthesis, promote starch metabolism and provide energy for seed germination. Environmental factors control the ratio of GA and ABA by regulating the biological activity of their related enzymes, thus regulating the germination of plant seeds.…”
Section: Introductionmentioning
confidence: 99%